Two Antibody-Guided Lactic-co-Glycolic Acid-Polyethylenimine (LGA-PEI) Nanoparticle Delivery Systems for Therapeutic Nucleic Acids - Jian-Ming Lü; Zhengdong Liang; Dongliang Liu; Bin Zhan; Qizhi Yao; Changyi Chen (MDPI AG, 2021)
We previously reported a new polymer, lactic-co-glycolic acid-polyethylenimine (LGA-PEI), as an improved nanoparticle (NP) delivery for therapeutic nucleic acids (TNAs). Here, we further developed two antibody (Ab)-conjugated LGA-PEI NP technologies for active-targeting delivery of TNAs. LGA-PEI was covalently conjugated with a single-chain variable fragment antibody (scFv) against mesothelin (MSLN), a biomarker for pancreatic cancer (PC), or a special Ab fragment crystallizable region-binding peptide (FcBP), which binds to any full Ab (IgG). TNAs used in the current study included tumor suppressor microRNA mimics (miR-198 and miR-520h) and non-coding RNA X-inactive specific transcript (XIST) fragments; green fluorescence protein gene (GFP plasmid DNA) was also used as an example of plasmid DNA. MSLN scFv-LGA-PEI NPs with TNAs significantly improved their binding and internalization in PC cells with high expression of MSLN in vitro and in vivo. Anti-epidermal growth factor receptor (EGFR) monoclonal Ab (Cetuximab) binding to FcBP-LGA-PEI showed active-targeting delivery of TNAs to EGFR-expressing PC cells.